Peningkatan Kualitas Literasi Akademik Mahasiswa melalui Pelatihan Reference Manager dan Pemetaan Literatur Digital - Yuni Sarah; Edriagus Saputra; Ammi Thoibah Nst; Rina Sari Lubis; Asrin Nasution; Muhammad Zia Alghar (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community service activity aims to improve students' academic literacy through training in the use of reference managers and digital literature mapping applications. Methodology: The method used in this community service was the ABCD model, conducted online via the Zoom Meeting Cloud platform, with 100 students from various study programs at STAIN Mandailing Natal participating. The activity included preparation, implementation, evaluation, and follow-up. Results: The results of the activity showed that students gained increased understanding and skills in using reference manager applications, and were able to utilize Scispace and Vosviewer to enrich their research insights. Furthermore, participants stated that this training was very useful in preparing scientific papers that were of higher quality, systematic, and met academic standards. Conclusions: This community service training proved relevant and effective, improving academic understanding, practical skills, and students’ readiness for career development and further academic study optimally overall. Limitations: This community service activity has several limitations, including its online implementation, large participant numbers, limited internet access, and short-term evaluations that have not yet measured long-term impacts on students’ scientific work. Contributions: This community service activity strengthens students’ academic literacy and research skills, especially in using reference managers and digital literature mapping tools to produce systematic scientific work at STAIN Mandailing Natal. It enhances understanding of academic writing, ethics, information management, and improves citation accuracy, research efficiency, and institutional research quality overall.